산겨릅나무 목질부에서 분리한 페놀성 화합물의 DPPH 라디칼 소거활성 - 권동주; Dong Joo Kwon; 김진규; Jin Kyu Kim; 배영수; Young Soo Bae (목재공학, 2011)
현재까지 산겨릅나무의 식물화학적인 연구는 수피부에 국한되어 있으며, 목질부의 성분연구는 전혀 보고된 것이 없다. 본 연구는 산겨릅나무 목질부로부터 2개의 flavan 3-ol, 3개의 phenolic acid/alcohol 및 2개의 cou-marin 화합물을 컬럼크로마토그래피를 연속적으로 실시하여 분리하였다. 화합물의 구조는 lH-NMR, 13C-NMR, 2D-NMR 및 MS 스펙트럼을 분석하여, (+)-catechin (1), (-)-epicatechin (2), p-hydroxybenzaldehyde (3), syringic alcohol(4), p-tyrosol(5), scopoletin(6) 및 cleomiscosin A (7)으로 동정하였으며, 그 중 p-hydroxybenzaldehyde(3), syringic alcohol(4), scopoletin(6) 및 cleomiscosin A (7)는 산겨릅나무에서는 처음 분리하였다. 화합물의 DPPH 라디칼 소거활성 측정 결과(+)- catechin (1)과(-)-epicatechin (2)은 양성 대조구로 사용한 BHA보다 우수한 항산화 활성을 나타냈다. There have been few reports on the constituents and biological activity of stem bark of Acer tegmentosum, and no phytochemical and biological studies have been reported for stem wood of A. tegmentosum. Two flavan 3-ols (1 and 2), three phenolic acid/alcohols (3~5), and two coumarins (6 and 7) were isolated from the stem wood of A. tegmentosum by repeated column chromatography. The structure of isolated compounds were identified as (+)-catechin (1), (-)-epicatechin (2), p-hydroxybenzaldehyde (3), syringic alcohol (4), p-tyrosol (5), scopoletin (6), and cleomiscosin A (7) on the basis of spectroscopic evidences such as 1H-NMR, 13C-NMR, 2D-NMR and MS spectrum. P-Hydroxybenzaldehyde (3), syringic alcohol (4), scopoletin (6), and cleomiscosin A (7) have not been reported from this plant so far. (+)-Catechin (1) and (-)-epicatechin (2) showed the higher 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity than hutylated hydroxyanisole (BHA) used as a positive control.